The Effect of Problem-Based Learning Assisted by Animated Video on Biology Students’ Creativity - Fitria Herawadini; Mahrus Mahrus; Rizkia Apriani; Khaerul Anam (Indonesian Journal of Educational Innovation, 2026)
Creativity is a key competency that needs to be developed through Biology learning to meet the demands of twenty-first-century education. This study aims to determine the effect of Problem-Based Learning (PBL) assisted by animated video on students’ creativity in Biology learning. The study employed a quantitative quasi-experimental design with a nonequivalent control group design, involving 50 Grade XI students divided into experimental and control classes. Data were collected using pretest and posttest instruments based on four creativity indicators, fluency, flexibility, originality, and elaboration, and analyzed using ANCOVA with pretest scores as covariates. The results show that students’ creativity in the experimental class increased significantly compared to the control class, with ANCOVA indicating a significant treatment effect (p < 0.05) and a large effect size. It can be concluded that PBL, assisted by animated video, is more effective than conventional learning at enhancing students’ creativity. These findings suggest that integrating problem-based learning with interactive digital media can be an effective strategy for fostering creativity and supporting the implementation of innovative, student-centered Biology learning.